When knowledge goes underground: Cultural information poverty, and Canada's Indian Act. - Edwards, Ashley (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2020)
The passing of the Indian Act in 1876 imposed cultural information poverty within Indigenous communities. Through this piece of Canadian legislation, Indigenous communities were forced to send their children to Residential Schools, and all cultural practices such as the potlatch and Sun Dance were banned. These policies disrupted education practices, and the passing down of information, creating a disconnect between younger generations and their communities. However the Indian Act’s goal of assimilation failed with some of these traditions going underground, being practiced in secret. Through strength and resilience communities today are experiencing a cultural revitalization, and what one Indigenous author calls a renaissance. The paper concludes by sharing ideas on how academic libraries can better engage with their local Indigenous communities.